Somaclonal Variation Among Somatic-Embryo Derived Plants of Olea europaea L “cv. Kroneiki” - M. Peyvandi (Journal of Sciences, Islamic Republic of Iran)
Frequency of somaclonal variation in embryogenic calli and plants of Olea europaea L cv.Kroneiki derived from somatic embryogenesis were examined by randomly amplified polymorphic DNA (RAPD) analysis. Radicle and cotyledon (proximal part) of mature zygotic embryo were cultured in OMc medium supplemented with IBA (5 mgL-1) and 2-ip (0.5 mgL-1). Somatic embryogenesis was induced in calli of radicles (55%) and proximal part of cotyledons (8%) on OM medium without any hormones. After culturing the embryogenic calli on OM medium in the presence of BAP (2 mgL-1), regenerated plants were obtained. DNA sample from the leave of the mother plants, seedlings (germinated from zygotic embryo), plantlets (regenerated from somatic embryo), embryogenic calli, non-embryogenic calli and zygotic embryos were subjected to RAPD analysis. 20 arbitrary decamer primers produced polymorphic amplification products. These primers gave a total of 315 reproducible fragments from which 221 (71%) were useful as polymorphic bands with an average of twelve RAPD marks obtained for each primer. A dandogram, based on the unweighted pair group mean average (UPGMA) method of cluster analysis, were constructed using a similarity matrix derived from the RAPD amplification generated by all primers. The estimation of genetic similarity coefficient based on RAPD band sharing data indicated that regenerated plants were less than 75% similar to mother plants.